2023
DOI: 10.1136/bmjresp-2022-001426
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating pain in survivors of critical illness: the correlation between the EQ-5D-5L and the Brief Pain Inventory

Abstract: IntroductionPain is a common and debilitating symptom in survivors of critical illness. The ‘Core Outcome Set for Survivors of Acute Respiratory Failure’ proposes that the pain and discomfort question of the EuroQol 5 Dimension 5 Level (EQ-5D-5L) could be used to assess pain in this group, however, it was recognised that further research is required to evaluate how this single question compares to other more detailed pain tools. This study aims to evaluate the relationship between the pain and discomfort quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Our dataset comprised more than 10,000 participants from 10 studies and took place across different stroke settings, thereby increasing overall generalisability of results when compared to studies based on single centres or settings. Similar work has established the moderate relationship between the EQ-5D pain domain and the Brief Pain Inventory, but was based on a much smaller sample size in a different health condition ( 40 ). Our population included people with language impairment due to stroke, thereby providing information on populations in whom measurement of pain can be particularly challenging.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Our dataset comprised more than 10,000 participants from 10 studies and took place across different stroke settings, thereby increasing overall generalisability of results when compared to studies based on single centres or settings. Similar work has established the moderate relationship between the EQ-5D pain domain and the Brief Pain Inventory, but was based on a much smaller sample size in a different health condition ( 40 ). Our population included people with language impairment due to stroke, thereby providing information on populations in whom measurement of pain can be particularly challenging.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, the NPRS showed high test–retest ability and is highly correlated with the pain Visual Analogue Scale (VAS) ( 39 ). Docherty et al ( 40 ) reported moderate correlation between the EQ-5D-5L pain and discomfort domain with the Brief Pain Inventory (BPI). A separate study in adult burn patients reported Spearman correlation of 0.468 between the EQ-5D-5L pain and discomfort domain and the Patient and Observer Scar Assessment Scale (POSAS) ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the EQ-5D-5L for the SAVE study is based on several considerations and criteria. Specifically, this quality-of-life assessment tool: 1) correlates well in comparison to instruments focused on symptoms amenable to palliative care such as pain, 72 2) strong psychometric properties and validation 73,74 across conditions and populations, 3) serves as a standard tool for comparison across study countries, 4) is available in multiple languages following standardized translation protocol in accordance with international guidelines for use across study sites worldwide, 75 and 5) poses low respondent burden. Any descriptive information provided by participants in administration of the EQ-5D-5L can be captured to further link with dominant qualitative arm of the study.…”
Section: Assessment Of Performance Status and Health-related Quality ...mentioning
confidence: 99%